(untitled) (BIRDEM Medical Journal, 2019)
Background: Threatened abortion is the most common complication in the first half of gestation. Spontaneous abortion occurs in less than 30% of the women who experience threatened abortion. In order to prevent pregnancy loss several supportive therapies including hormonal therapy like human chorionic gonadotropin (hCG) or 17-alpha-hydroxyprogesterone (progesterone) have been advocated. The exogenous administration of hCG is aimed at stimulating and therefore optimizing progesterone production. Aim of this study was to compare the efficacy of supportive therapy with hCG and progesterone in women with threatened abortion. Methods: This prospective study was carried out in the department of obstetrics and gynecology of the Combined Military hospital (CMH), Savar, Dhaka, Bangladesh from July 2016 to June 2017. One hundred pregnant patients admitted with the history of per vaginal bleeding before 20 weeks of gestation without having any other co-morbidity were included in this study. Patients were randomized to two treatment groups. The participants in group A (52, 52%) received injection hCG weekly while those in group B (48, 48%) received injection progesterone from recruitment up until 20 weeks of gestation. Further USG were performed one week and four weeks after recruitment to the study and again at 20 weeks and subsequently when indicated. The final outcome of pregnancy were recorded and analyzed. Results: Among 100 patients majority belonged to the 26-30 year age group. Mean age of the patients was 27.2±10.5 years. There was not much significant difference between the groups in terms of parity. More than 75% of patients in both the groups presented before 16 weeks of gestation with threatened abortion. In both the groups more than 75% of the patients had previous history of pregnancy loss. In terms of pregnancy outcome more patients in hCG group had live pregnancy than progesterone group (88.5% vs 66.7%) (p=0.012). Out of 46 live birth in hCG group, 4 (7.7%) were preterm labor between 31-35 weeks of pregnancy and one baby died in neonatal ICU, one died at 31 weeks of gestation which was delivered by vaginally. On the other hand out of 32 live birth in progesterone group, there was 3 (6.3%) preterm labor. Growth retardation was less in hCG group compared to progesterone group (9.6% vs 14.6%). However cesarean section rate was high in both the groups. Conclusion: Treatment with injection hCG has better pregnancy outcome than that of injection17-alphahydroxyprogesterone in early pregnancy with threatened abortion of unexplained cause. Birdem Med J 2019; 9(1): 7-10